Naturally occurring mutations in the PA gene are key contributors to increased virulence of pandemic H1N1/09 influenza virus in mice - Sun, Y.; Xu, Q.; Shen, Y.; Liu, L.; Wei, K.; Sun, H.; Pu, J.; Chang, K.-C.; Liu, J. (American Society for Microbiology, 2014)
We examined the molecular basis of virulence of pandemic H1N1/09 influenza viruses by reverse genetics based on two H1N1/09 virus isolates (A/California/04/2009 [CA04] and A/swine/Shandong/731/2009 [SD731]) with contrasting pathogenicities in mice. We found that four amino acid mutations (P224S in the PA protein [PA-P224S], PB2-T588I, NA-V106I, and NS1-I123V) contributed to the lethal phenotype of SD731. In particular, the PA-P224S mutation when combined with PA-A70V in CA04 drastically reduced the virus's 50% mouse lethal dose (LD50), by almost 1,000-fold.